Post a New Question

trig

posted by .

sorry -- here it is
simplify this expression : (x^3 y)/(y^(1/2) x^(-2) ) when x is not = 0, and y is not equal to 0

thank you

  • trig -

    WE know that [formula a^m/a^n=a^(m-n)]
    where m>n it means in division when base (means 'a') are same with different power('m' and 'n') then powers are subtracted

    x^3*y/[(y^1/2)*(x^-2)]

    =x^3-(-2)*y^(1-1/2)

    =x^3+2*y^1/2

    =x^5*y^1/2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question